Human serum albumin: A modulator of cannabinoid drugs. Issue 11 (4th October 2017) - Leboffe, Loris; di Masi, Alessandra; Trezza, Viviana; Polticelli, Fabio; Ascenzi, Paolo
Abstract: The endocannabinoid system is a unique neuromodulatory system that affects a wide range of biological processes and maintains the homeostasis in all mammal body systems. In recent years, several pharmacological tools to target endocannabinoid neurotransmission have been developed, including direct and indirect cannabinoid agonists and cannabinoid antagonists. Due to their hydrophobic nature, cannabinoid agonists and antagonists need to bind specific transporters to allow their distribution in body fluids. Human serum albumin (HSA), the most abundant plasma protein, is a key determinant of drug pharmacokinetics. As HSA binds both the endocannabinoid anandamide and the active ingredient of Cannabis sativa, Δ‐9‐tetrahydrocannabinol, we hypothesize that HSA can be the most important carrier of cannabinoid drugs. In silico docking observations strongly indicate that HSA avidly binds the indirect cannabinoid agonists URB597, AM5206, JZL184, JZL195, and AM404, the direct cannabinoid agonists WIN55, 212-2 and CP55, 940, and the prototypical cannabinoid antagonist/inverse agonist SR141716. Values of the free energy for cannabinoid drugs binding to HSA range between −5.4 kcal mol –1 and −10.9 kcal mol –1 . Accounting for the HSA concentration in vivo (∼ 7.5 × 10 –4 M), values of the free energy here determined suggest that the formation of the HSA:cannabinoid drug complexes may occur in vivo . Therefore, HSA appears to be an important determinant for cannabinoid efficacy and may guide the choice of the drug dose regimen to optimize drug efficacy and to avoid drug‐related toxicity. © 2017 IUBMB Life, 69(11):834–840, 2017.